Bank Kerjasama Rakyat Malaysia Berhad / Alisa Syafawati Mohd Azri - Mohd Azri, Alisa Syafawati (Faculty of Business and Management, 2023)
An industrial training plays a vital role as it helps students to get a clearer picture of the career world. It is the initial move for students to gain the realistic knowledge, skills, and experience in the real world of work. Internships are designed to provide opportunities for students to equip themselves with valuable experience at the workplace. The second part of the report shows an updated resume of the intern according to the latest working experience that she has gained during her internship, while the third part of the report provides an overview of the company’s profile. Furthermore, the fourth part covers the training’s reflection where the student shares regarding the department she has been placed and the tasks that have been assigned to her. In addition, the fifth part of the report is crucial as it illustrates the SWOT analysis that has been analysed by the intern herself. This part describes two strengths, two weaknesses, two potential opportunities and two prospective threats of Bank Kerjasama Rakyat Malaysia Berhad. The next part discusses two recommendations that have been suggested by the intern which she thinks and believes that they would be beneficial for Bank Kerjasama Rakyat Malaysia Berhad to improve which might help to maximize profitability and minimize loss. At the end of the report, the intern shared her final thoughts regarding her 24 weeks of internship at Bank Kerjasama Rakyat Malaysia Berhad. Overall, the intern obtained valuable knowledge, skills and experience in the workplace throughout her internship with Bank Kerjasama Rakyat Malaysia Berhad, which allows her to put her studies in Human Resource Management at UiTM into practice.